2019
DOI: 10.1007/s12178-019-09576-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing in Minimally Invasive Spine Surgery

Abstract: Purpose of Review To summarize the recent advances in 3D printing technology as it relates to spine surgery and how it can be applied to minimally invasive spine surgery. Recent Findings Most early literature about 3D printing in spine surgery was focused on reconstructing biomodels based on patient imaging. These biomodels were used to simulate complex pathology preoperatively. The focus has shifted to guides, templates, and implants that can be used during surgery and are specific to patient anatomy. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…9) For surgical planning, 3D printing provides better understanding of complex spinal deformities. 9,11,13,14) The present cases in which FELF was performed are re-operation case or high-iliac L5-S cases, in which 3D printing was useful for planning the cannula approach and the shaving extent of the SAP. Transforaminal approach of the L5-S and L4-L5 level with high iliac crest, which interferes with the cannula placement, is difficult, 6) and 3D printings could be useful.…”
Section: Discussionmentioning
confidence: 97%
“…9) For surgical planning, 3D printing provides better understanding of complex spinal deformities. 9,11,13,14) The present cases in which FELF was performed are re-operation case or high-iliac L5-S cases, in which 3D printing was useful for planning the cannula approach and the shaving extent of the SAP. Transforaminal approach of the L5-S and L4-L5 level with high iliac crest, which interferes with the cannula placement, is difficult, 6) and 3D printings could be useful.…”
Section: Discussionmentioning
confidence: 97%
“…In order to determine the ideal transosseous tunnels between the clavicle and the coracoid process, many studies have researched the anatomical characteristic of coracoclavicular ligament. In that case, our research designed an individualized 3D printed guide design, which is placed on the exposed clavicle helping to find the precise anatomical location of the transosseous tunnel drilling during the operation 12 , 13 , 23 . At the same time, compared with conventional operation, this method can improve the accuracy of drilling and reduce the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the triple Endobutton technology has solved many problems, there are still some shortcomings, such as the length of the fiber suture cannot be adjusted at will. With the increasing development of three‐dimensional (3D) printing technology, some orthopaedic surgeons gradually apply it to clinical work to give patients a specific treatment without causing too much trauma, because it could provide anatomical details of various bones and tissues 12 , 13 . At present, the use of 3D printing technology to process ACD has made some significant progress, creating individualized guided design and trying to determine the ideal location of the transosseous tunnel 14 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have indicated that in cardiac and vascular surgery, 3DP technology provides a characteristic patient-specific model that recognizes complex anatomy and is helpful for injury orientation, plan-making, and communication with patients [63] . In addition, much research has shown that 3DP plays a vital role in the preoperative preparation for dental surgery, orthopedic surgery, spine surgery, urological surgery, and some tumor surgeries, from strengthening preoperative planning to enhancing the operator's confidence for the surgery [64][65][66][67] . Not only in the preoperative preparation but also during the surgical period, 3DP still plays a crucial role in its next stage-Surgical Guide.…”
Section: Three-dimensional Printing (3dp)mentioning
confidence: 99%